EXAMINING THE TEMPORAL ASSOCIATIONS BETWEEN SUBJECTIVE MEMORY IMPAIRMENT AND DEPRESSIVE SYMPTOMS IN OLDER ADULTS. (11th November 2018) - Bhang, I; Mogle, J; Hill, N; Whitaker, E; Bhargava, S; Barnes, L
Abstract: Older adults commonly report problems with their memory (i.e., subjective memory impairment or SMI) which can elicit sadness and worry about future development of cognitive impairment. Conversely, depressive symptoms can negatively impact perceptions of memory performance. The current study examined the temporal links between SMI and depressive symptoms to explore which tends to appear first. Older adults (n=1724; Mage=77.0; SD=7.5; 76.8% Female; 32.1% Black) completed yearly assessments of SMI (perceived decline, frequency of problems) and depressive symptoms for up to 18 years. Concurrently, SMI and depressive symptoms were significantly related; at times when SMI was higher, older adults also reported more depressive symptoms, regardless of SMI assessment. Prospectively, depressive symptoms predicted future SMI reports of memory decline, but not frequency of problems. Similarly, only perceived memory decline predicted future depressive symptoms. This study highlights the complex temporal association between SMI and depressive symptoms, and provides recommendations for assessing SMI.